COVID-19 in Palestine: What International Laws Can Offer? - Mohamad Kamal Sodiqin Abdull Manaf; Nisar Mohammad Ahmad (USIM Press, 2024)
Vol. 33 No. 3 (2021): ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences